2005
DOI: 10.1002/jctb.1349
|View full text |Cite
|
Sign up to set email alerts
|

Studies on the oxidation of phenols catalyzed by a copper(II)–Schiff base complex in aqueous solution under mild conditions

Abstract: The catalytic oxidation of phenol with hydrogen peroxide using a synthetic copper(II)-Schiff base complex as catalyst has been investigated in phosphate buffer at pH 7 and 25• C. In order to further investigate the reaction pathway, the catalytic oxidation of hydroquinone, p-benzoquinone and catechol were also studied under the same conditions. These reactions were found to be pseudo-first-order with respect to the concentration of phenolic substances. The rate constants were also calculated. In the presence o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2007
2007
2014
2014

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 33 publications
(10 citation statements)
references
References 24 publications
0
10
0
Order By: Relevance
“…Conditions for first-order kinetics are fulfilled as presented in Case 1 of the kinetic model. 31 Kondru et al (2009) 32 and Meng et al (2006). 33 In this work, a catalyst concentration of 500 ± 5 mg L −1 was suggested as the optimum value since higher catalyst concentrations gave almost similar results.…”
Section: Effect Of Initial Dye Concentrationmentioning
confidence: 82%
“…Conditions for first-order kinetics are fulfilled as presented in Case 1 of the kinetic model. 31 Kondru et al (2009) 32 and Meng et al (2006). 33 In this work, a catalyst concentration of 500 ± 5 mg L −1 was suggested as the optimum value since higher catalyst concentrations gave almost similar results.…”
Section: Effect Of Initial Dye Concentrationmentioning
confidence: 82%
“…Zhou et al (2004) observed that the photo-oxidation efficiencies were dependent on pH values and ferric/oxalate concentration ratios in water. Meng et al (2006) indicated that oxidation of phenols catalyzed by a copper Schiff base complex in aqueous solution. Target compounds With 0.5 M scavenger Without scavenger Fig.…”
Section: Verification Of the Role Of •Oh Radicalmentioning
confidence: 98%
“…Sykora [24] reviewed the photochemical behavior of copper complexes and indicated that the presence of Cu 2+ and another reactant (catalyst) can lead to enhancement of pollutant photodegradation. Meng et al [25] studied on the oxidation of phenols catalyzed by a copper ( )-schiff base complex in aqueous solution. Uchida and Kawakishi [26] investigated the degradation of ȕ-cyclodextrin induced by Cu 2+ in the presence of ascorbic acid.…”
Section: Introductionmentioning
confidence: 99%